Indicadores e índice para evaluar la degradación en suelos de tipo andosol y molisol en ecosistemas andinos y el avance de la frontera agrícola. - Hualpa Piñas, Dennys Josuet (2022)
This research aimed to apply a minimum set of physical and chemical indicators to evaluate soil quality in Andean ecosystems. A set of soil samples were taken in the province of Chimborazo in the sectors of Achupallas, Pomacocho, La Esperanza and Llucud, which have soils of the order Andosol and Molisol. Using physical indicators, the result was a change in the soil DBH under páramo (0.53 g/cm3) and its transition to cultivation, 1.44 (g/cm3). In the same way, the stable macroaggregates in páramo was 68.43 %, while in cultivation over 10 years it was 19.76 %. Chemical indicators used were pH, which reported a value of 4.96 for cultivation and 5.07 for páramo; the total organic carbon content (TOC) was 24.67 in páramo and 5.09 in cultivation, both with low values related to inappropriate tillage and agricultural practices that cause consumption of organic matter (OM) and release of carbon (C) to the atmosphere in the form of CO2. The ICs soil quality index was calculated using the WSA (Weighted Sum Analysis) method. According to the results of the indices of physical and chemical parameters, soils under cultivation and pasture are the most degraded compared to soils under páramo.